The relationship between e-learning and student satisfaction as marketing strategy: A case study at a private university - Soeryanto Soegoto, Eddy; Luckyardi, Senny; Jumansyah, Rizky; Saputra, Herry; Kruger, Niël A (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
Universities have incorporated e-learning into their educational structures because of the unanticipated transition from conventional learning to digital and hybrid learning methods to the closure of educational facilities during the COVID-19 pandemic. This study aims to ascertain how e-learning influences students’ satisfaction at private universities and to develop a marketing strategy to keep institutions of higher learning competitive throughout the COVID-19 or similarly disrupting events. In the study, we utilise a quantitative descriptive method. Collecting data was done by distributing e-questionnaires to students at a private university in Bandung. The sampling technique used random sampling with 245 respondents. The data was subjected to numerous linear regression analyses using SPSS. ICT, ESQ, and EIQ are the study’s dependent variables, and e-learning is the study’s independent variable. The findings indicate that all variables influence and significance of e-learning and students’ satisfaction with 65.9%, which can enhance learning outcomes in private universities.